2020
DOI: 10.1088/1741-4326/ab5cd4
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium retention in Sn-filled samples exposed to fusion-relevant flux plasmas

Abstract: Tin (Sn) is an attractive option for a liquid metal wall material for future fusion reactors. Control of tritium inventory is key for the successful operation of these reactors, but little data exists up until now on hydrogen isotope retention in Sn. Free surface Sn targets and Sn-based capillary porous structure targets were exposed to deuterium (D) plasma in nano-PSI and magnum-PSI respectively. The retained D inventory was determined using the methods of thermal desorption spectroscopy and nuclear reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
42
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 47 publications
17
42
5
Order By: Relevance
“…One extreme example is bubble formation due to liquid boiling at boiling point. In our previous work [25], we have observed Sn droplet ejection due to boiling in vacuum of 10 -5 Pa at T ~ 800 °C .…”
Section: Bubble Formation and Growth In Supersaturated Liquidmentioning
confidence: 90%
See 3 more Smart Citations
“…One extreme example is bubble formation due to liquid boiling at boiling point. In our previous work [25], we have observed Sn droplet ejection due to boiling in vacuum of 10 -5 Pa at T ~ 800 °C .…”
Section: Bubble Formation and Growth In Supersaturated Liquidmentioning
confidence: 90%
“…In [40], Duchemin also simulated the bubble bursting process and concluded that the radius of the first droplet due to jet formation is about 10% of the initial bubbles radius. In [25], the pits in the range of 0.1 -1 µm are observed on Sn surface after exposure. 1 µm-scaled bubbles in liquid Sn exposed to hydrogen plasma are also reported by Ruzic [28].…”
Section: Bubble Formation and Growth In Supersaturated Liquidmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding the H retention of the liquid Sn, the results that can be found in literature are rather discordant: very low retention was found in [4], while higher values are reported in [5] and [6]. In any case, even the most pessimistic results are not such as to discourage the use of Sn.…”
Section: Introductionmentioning
confidence: 87%